The Effectiveness of Schema Therapy on Depression and Cognitive Emotion Regulation in Adolescents with Psychosomatic Disorders - Ahangaran , Alireza; Zoghi Paidar, Mohammad Reza (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: This study aimed to determine the effectiveness of schema therapy in reducing depression and improving cognitive emotion regulation among adolescents with psychosomatic disorders.Methods and Materials: This quasi-experimental study used a pre-test, post-test, and two-month follow-up design with a control group. The statistical population included adolescents with psychosomatic disorders who referred to specialized psychology clinics in Hamedan. Thirty participants were selected through convenience sampling and randomly assigned to an experimental group and a control group, with 15 participants in each group. The experimental group received schema therapy in ten 90-minute sessions, whereas the control group received no psychological intervention during the study period. Data were collected using the Depression Scale and the Cognitive Emotion Regulation Questionnaire. Data analysis was conducted using SPSS version 26 through repeated-measures two-way analysis of variance after checking the assumptions of normality, homogeneity of variance, sphericity, and equality of covariance matrices.Findings: The results showed a significant between-group effect for depression (F = 4.688, p = 0.033, η² = 0.27) and cognitive emotion regulation (F = 15.703, p = 0.024, η² = 0.204). The within-group effect of time was also significant for depression (F = 24.416, p < 0.001, η² = 0.67) and cognitive emotion regulation (F = 36.997, p < 0.001, η² = 0.785). Moreover, the group-by-time interaction effect was significant for depression (F = 60.000, p < 0.001, η² = 0.71) and cognitive emotion regulation (F = 66.011, p < 0.001, η² = 0.653), indicating the effectiveness of schema therapy across post-test and follow-up stages.Conclusion: Schema therapy appears to be an effective psychological intervention for reducing depression and enhancing cognitive emotion regulation in adolescents with psychosomatic disorders. By targeting early maladaptive schemas and modifying dysfunctional cognitive-emotional patterns, this approach can contribute to improved psychological functioning in this population.